ANALISIS PENERAPAN STANDAR AKUNTANSI PEMERINTAH (SAP) DALAM LAPORAN KEUANGAN INSPEKTORAT JENDERAL KEMENTERIAN HUKUM DAN HAM - Febriani, Ine; Gurrendrawati , Etty; Armeliza, Diah (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to analyze the implementation of government accounting standards in the financial statements of the Inspectorate General of the Ministry of Law and Human Rights. The study focuses on the application and conformity, as well as the quality of government financial statements from 2022 through 2023. The research sample uses purposive sampling, consisting of employees from the accounting and finance division, as well as the financial statement preparation team. The results show that the implementation of PSAP 01 in the financial statements produced by the Inspectorate General of the Ministry of Law and Human Rights is efficient, and the financial reports comply with applicable regulations, making them accountable. The percentage of conformity with SAP in the financial statements of the Inspectorate General is 95.65%. Although the financial statements of the Inspectorate General are in accordance with the applicable SAP, the quality of the reports is not yet perfect, which affects the accountability of the reports. There are still some inaccurate pieces of information in the audits, such as insufficient internal control and a lack of clear separation of duties between financial managers and supervisors. A significant finding is that the staff involved in preparing the financial statements do not fully understand SAP. The financial statements of the Inspectorate General of the Ministry of Law and Human Rights comply with the SAP applied by the government, with financial statement components including the Budget Realization Report, Changes in SAL Report, Balance Sheet, Operational Report, Changes in Equity Report, and Notes to the Financial Statements.